(3fXQjI eMGSHjIs - (3GMeO QjGMj(B, (3HdbGhjs; (3QjGV(B, (3YHO Gddgs ((3YeGf(B:s (3OGQ GdjGRhQj(B,s, 2009)
(3JGQjN GdeMGSHI h JWhQgG , WHjYJgG h GSJNOGeGJgG , GdeOGNd GdJbdjOjI dUjGZI GdfXQjI GdeMGSHjI , GdeONd GdJhLjgj GdeQcRj dUjGZI gPg GdfXQjI , GdGWGQ GdacQj ddeMGSHI h GdGHdGZ GdeGdj , gjWd GdfXQjI GdeMGSHjI , GdGfUGa h GdGaUGM h GdGJLGgGJ GdeSJbHdjI aj GdeMGSHI (B.s
(3GdeQGLY U(B.439((3GbJfGAGJ (B2014 3(3f(B)s
Keywords: (3GdeMGSHIs